Ewing Sarcoma With Emphasis on Extra-skeletal Ewing Sarcoma: A Decade's Experience From a Single Centre in India - Sudha S Murthy; S Challa; KVVN Raju; SJ Rajappa; D Fonseca; SD Gundimeda; BV Rao; F Ahmed; S Kodandapani; L Nambaru; MC Mundada; R Sharma; et al. (SAGE Publishing, 2020)
Introduction: The diagnosis of Ewing sarcoma family of tumours (ESFT) is challenging, especially in adults and in extra-skeletal or visceral location. Several morphologic mimics with varied treatment options and prognosis confer diagnostic dilemmas. Application of ancillary diagnostic modalities in surgical pathology in clinical routine has enabled accurate diagnosis of ESFT in bone, soft tissues, and viscera. Aim: The study aims to assess the clinicopathological features including molecular test results of ESFT with emphasis on sex, age, and location, especially extra-skeletal soft tissue and visceral location. Material and Methods: Data of clinicopathological, molecular tests (wherever performed), diagnosis rendered in 302 ESFT over a decade from our centre were reviewed. Statistical comparison of skeletal and extra-skeletal tumours with reference to age and sex was done using SPSS package. The P value of <.05 was considered significant. Results: The cohort included 302 ESFTs with 49% skeletal and 51% extra-skeletal tumours. Thigh was most common site among skeletal tumours; chest wall, paraspinal location, and retroperitoneum among soft tissues (39.4%); and kidney, ovary, and cervix among visceral tumours (11.3%). Fluorescence in situ hybridisation for EWSR1 gene rearrangement was positive in 54 patients and reverse-transcriptase polymerase chain reaction in 19 patients. Predominance of male sex, younger age and location in extremities among skeletal tumours and lack of gender predilection, higher age and axial location in extra-skeletal tumours were noted, which were statistically significant. Molecular tests were performed more frequently in extra-skeletal tumours, especially in visceral tumours to establish the diagnosis. Conclusions: The study showed statistically significant differences in the age, sex, and location between skeletal and extra-skeletal ESFT. The increased percentage of extra-skeletal tumours especially in viscera was attributed to the increased awareness and availability of ancillary techniques.